Human Extinction and the Pandemic Imaginary - Lynteris, Christos (Routledge Studies in Anthropology, 2020)
This book develops an examination and critique of human extinction as a result of the 'next pandemic' and turns attention towards the role of pandemic catastrophe in the renegotiation of what it means to be human. Nested in debates in anthropology, philosophy, social theory and global health, the book argues that fear of and fascination with the 'next pandemic' stem not so much from an anticipation of a biological extinction of the human species, as from an expectation of the loss of mastery over human/non-humanl relations. Christos Lynteris employs the notion of the 'pandemic imaginary' in order to understand the way in which pandemic-borne human extinction refashions our understanding of humanity and its place in the world. The book challenges us to think how cosmological, aesthetic, ontological and political aspects of pandemic catastrophe are intertwined. The chapters examine the vital entanglement of epidemiological studies, popular culture, modes of scientific visualisation, and pandemic preparedness campaigns. This volume will be relevant for scholars and advanced students of anthropology as well as global health, and for many others interested in catastrophe, the 'end of the world' and the (post)apocalyptic.